CONCEPT MAPPING CARE PLAN (CMCP): AN APPROACH TO IMPROVING THE ACADEMIC PERFORMANCE AMONG NURSING STUDENTS IN THE CLINICAL SETTING - Rusnani Ab Latif; Wan Ismahanisa Ismail; Yoyok Bekti Prasetyo; Abd Nasir; Jamilah Shaari (Universitas Airlangga, 2026)
Introduction: Applying knowledge and skills taught in classrooms into practice is a crucial aspect of nursing education, known as clinical practice. The successful completion of this application procedure will allow them to effectively connect the disparities between theoretical knowledge and practical experience, thus enhancing their skills and expertise in clinical decision-making. Prior research indicated that 70.7% of the participants could apply their classroom learning to their clinical practice. Concept mapping is an advantageous instrument for creating a treatment plan for a patient that is both coherent and systematic. Aims: The main objective of this research study is to evaluate the effectiveness of the CMCP in clinical settings. Methods: This study employed a quasi-experimental design and included a sample of 218 second-year nursing students, with 109 participants in each group. Respondents were randomly recruited to either a control group, which received a lecture-based intervention, or an experimental group, which received a concept mapping intervention. The respondents were chosen from areas within four nursing colleges affiliated with Institut Latihan Kementerian Kesihatan Malaysia (ILKKM). A p-value less than 0.05 was considered to be significantly different. Result: In clinical practices, the experimental group scored a CMCP score of 65.23, while the control group scored 59.33. The paired t-test (p < 0.05) observed significant statistical differences between the experimental and control groups. Conclusions: Concept mapping is essential for educators in nursing seeking to enhance their students' comprehension, apply theoretical information in clinical rotations, and develop understanding through enhanced conceptual connections.